Fatigue Performance of Sugar Palm Fibre-Reinforced Thermoplastic Polyurethane Composites with Varying Fibre Content - Bachtiar, Dandi; Siregar, Januar Parlaungan; Suhaeri; Masri; Zulfadhli (Journal of Engineering and Science, 2025)
This study investigates the fatigue behavior of sugar palm fibre (SPF)-reinforced thermoplastic polyurethane (TPU) composites with varying fibre contents (10 wt%, 20 wt%, and 30 wt%). The composites were fabricated using extrusion followed by hot press moulding. Tensile tests were conducted in accordance with ASTM D638 to determine the ultimate tensile strength (UTS), and fatigue tests were performed under stress levels of 80%, 70%, 60%, and 50% of the UTS, following ASTM D7791. The results indicate that an increase in fibre content leads to a reduction in both tensile strength and fatigue life, likely due to poor interfacial bonding and fibre agglomeration. Fatigue life was found to be significantly higher at lower stress levels across all fibre contents. These findings provide valuable information about the potential and limitations of SPF/TPU composites for applications involving cyclic loading, particularly in lightweight and sustainable material applications